Narcotics in Rheumatology - Mahsa Tehrani; Mathia Aguiar; James D. Katz (SAGE Publishing, 2013)
Patients with rheumatic conditions often suffer from related chronic pain. When first-line traditional medications such as acetaminophen and anti-inflammatory medications do not suffice, then other options are needed. The traditional medications may ultimately not provide sufficient pain relief, or alternatively, they can pose as a contraindication due to underlying hypertension, renal, and/or hepatic disease. Therefore, narcotics are an alluring alternative, which if used in a multidisciplinary and systematic approach to the patient, can prove to be quite beneficial in the lives of these patients.